METABOLIC THERAPY FOR PATIENTS WITH COEXISTING VISCERAL AND PERIODONTAL DISEASES - I. A. Gorbacheva; Yu. A. Sycheva; L. Yu. Orekhova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2017)
Introduction. Nowadays, many evidences about interrelation of inflammatory defeats of parodont and various internal diseases have been collected. Universal molecular and cellular deviations, violations of redox metabolism, pathological activation of apoptosis promote development and progressing of many somatic diseases and the inflammatory diseases of parodont associated with them.The objective is to evaluate the efficacy of metabolic therapy in patients with coexisting visceral and periodontal diseases.Materials and methods. 909 patients with visceral diseases associated with generalized periodontitis were examined totally. Group I consisted of 100 patients with chronic infection sites of different localization. Group II consisted of 100 patients with cardiovascular diseasesю Patients from group I and II were divided into two sub-groups, they were prescribed to take metabolic drugs – mexidol (ethylmethylhydroxypyridine succinate) or сycloferon (meglumine acridonacitate) and mildronate (meldonium dehydrate) or cytoflavin (drug succinic acid). Intensity of free radical oxidation in organism was assessed by the products of lipid peroxidation; oxidation of thiol-containing compounds – proteins and low-molecular thiols – was assessed by using direct and back amperometric titration; apoptosis was studied on the model of lymph cells using flow cytometry (Annexin V – FITC); the status of periodontium was assessed with definition of the periodontal index (PI) and community periodontal index of treatment needs (CPITN).Results. The activity of lipid peroxidation and free radical oxidation of thiols (р<0.01), the level of markers of pathological apoptosis Annexinа V – FITC (р<0.05) were increased in patients with coexisting visceral and periodontal diseases. In the course of the treatment with different metabolic medicines, the activity of lipid peroxidation tended to slow down as identified in both groups of examined patients (p<0.01) and increase thiol-disulfide ratio. In the course of treatment with metabolic drug, the number of cells entering apoptotic phase in patients with visceral and periodontal diseases was significantly fewer (р<0.01).Conclusions. Thus, the findings of the study demonstrate that the correction of specific deficiencies of homeostasis is accompanied by simultaneous correction of other homeostatic failures. Patient-specific approach in choosing the metabolic therapy for treatment of patients with coexisting visceral and periodontal diseases depends on the links of metabolic homeostasis where more significant deficiencies were revealed.